2014
DOI: 10.1155/2014/597357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on the Calcium and Magnesium Content, Lipid Peroxidation Level, and Ca2+-ATPase Activity of Syncytiotrophoblast Plasma Membranes from Placental Explants

Abstract: In the current study the possible relationship between the Ca2+/Mg2+ ratio of human syncytiotrophoblast plasma membranes and their lipid peroxidation and Ca2+-ATPase activity was determined. Syncytiotrophoblast plasma membranes of placental explants cultured under hypoxia increased their lipid peroxidation and Ca2+ content, diminished their Ca2+-ATPase activity, and kept their Mg2+ content unchanged. Membranes preincubated with different concentrations of Ca2+ increased their Ca2+ content without changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
14
3
Order By: Relevance
“…Therefore, these results suggest that MgSO 4 components are mainly adsorbed on the hydrophilic part of the surface membrane. This agrees with the experimental findings of Chiarello et al The authors proposed that magnesium might exert a stabilizing effect on the membrane, avoiding their exposure to free radicals. In this sense, the results of WDD for POPC, MgSO 4 , and • OH show a similar picture to the sum of the separated systems.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, these results suggest that MgSO 4 components are mainly adsorbed on the hydrophilic part of the surface membrane. This agrees with the experimental findings of Chiarello et al The authors proposed that magnesium might exert a stabilizing effect on the membrane, avoiding their exposure to free radicals. In this sense, the results of WDD for POPC, MgSO 4 , and • OH show a similar picture to the sum of the separated systems.…”
Section: Resultssupporting
confidence: 92%
“…Applications of magnesium sulfate for studying the antioxidant effect against LPO have been the object of study in several research articles . Maulik et al found that guinea pig brain cells under hypoxic conditions have increased LPO and that post‐treatment hypoxia with MgSO 4 reverses these effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that MgSO 4 treatment increased expression of both PMCA and SERCA-2 in BeWo cells. Chiarello et al insisted that MgSO 4 treatment in normal placental explants stabilized the Ca 2+ concentration with an increase in Mg 2+ concentration, and its treatment under hypoxic conditions decreased lipid peroxidation levels with an increase in PMCA activity eventually protecting the ST 22. In our study, however, MgSO 4 treatment under CoCl 2 treatment could not significantly increase PMCA expression, and it even decreased SECA-2 expression in BeWo cells.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the mechanism by which apoD influences PMCA-2 levels remains to be determined. As the increase of intracellular Ca 2+ content by excitotoxicity stimulates the generation of reactive oxygen species [77] and lipid peroxidation, which in turn downregulates rapidly PMCA levels [78], it is possible that apoD affects PMCA-2 levels through its anti-oxidant properties. Indeed, apoD and its orthologs have been shown to protect from pro-oxidative insults in several organisms [17][18][19]22].…”
Section: Discussionmentioning
confidence: 99%